The subdivided units phenomenon : can the 2013 LTHS solve the problems? - Ma, Sik-ho, Danald (The University of Hong Kong (Pokfulam, Hong Kong), 2015)
Sub-divided units (SDU) and the similar type of tiny accommodation namely cage home and cubicle apartment have been existed in Hong Kong for a long period of time. Despite the factthat the living condition of those flats is usually undesirable, there are views in the community that there is demand in the market because these flats can provide affordable urban accommodation to those who are not eligible for Public Rental Housing (PRH) or those who wish to live in the urban area which is closer to their workplaces or their children's place of study at a cheaper rent. The repeated fire incidents happened in the tenement buildings consisted of SDU causing number of casualties has widely aroused the public concern about the safety of SDU. Although the HK government has been implementing measures since 2011 to tackle the problems of SDU, the number of people living in SDU has still greatly increased from 53,000 in 2007 to 171,300 in 2013, accounting for 2.4% total population of Hong Kong. In fact, the increase of SDU not only reflects that many low-income group cannot afford the high housing rent, but also many households are being forced into inappropriate or sub-standard accommodation. J Pynoons, R Schafer, C Hartman (2012) stated that the quality and location of housing affect the security, happiness, and stability of families, and have serious implications for the economic and social wellbeing of our urban areas. The problems arising from SDUs not only affect the individual of tenants, but also impose hazard to the building management, fire safety, building structure and social order. Due to speculation and limited land supply, the problems of SDUs were still remained unsettled and the housing price has still been escalating to a higher recorded price causing shortage of adequate housing supply and thus the increase of rental price on housing. With rents escalating and Housing Authority waiting lists lengthening, low income households, particular the households who were not eligible to or awaiting for PRH were forced into inappropriate and sub-standard accommodation. Although the government has formed a long Term Housing Strategy (LTHS) Steering Committee to look into the housing problems of grassroots families, it would not see the proposed measures shall immediately solve the housing problems, particularly in relation to SDUs within a short period of time. All the proposed measures require number of years to plan, discuss and compromise with different parties. The goal of this dissertation is to review the phenomenon of SDU and to study the reasons of trend of such phenomenon. Without a thorough understanding on the phenomenon of SDU and the reasons of trend, no proper measures shall be implemented to tackle the problems of SDU. The phenomenon of SDU shall be deemed to be the result of number of reasons relating to land supply and housing demand. The ever rising housing price, the attitude and direction of property developers, the housing policy towards affordable housing and the high cost of living are the factors affecting the supply and demand of affordable housing whereas decreasing vacancy in the private rental market, lack of funding, lack of private development of affordable housing, increasing rent prices, lack of long-term affordable housing planning and the absence of a comprehensive housing policy cause the supply of affordable housing cannot meet the increasing demand. Besides, the attitude of people who worried that affordable housing will increase traffic, reduce their property values and lack of safety in their communities, no one wants to be near or to have additional affordable housing in their communities. These attitudes further make the government difficult to find suitable locations for affordable housing. Besides, various articles and news revealed that many people living in SDU are single parenthood, mental illness, disable and addiction to drugs and drink. However, there is no survey to reflect or indicate the real situation. Government should look into the real situation and to effect proper measures to tackle the problems of the above people. === published_or_final_version === Housing Management === Master === Master of Housing Management